Motivasi Belajar pada Remaja yang Diasuh oleh Ibu Tunggal - Meirry Rahmawati; Widyaning Hapsari; Patria Jati Kusuma (STIKes Ibnu Sina Ajibarang, 2023)
This study aims to determine how learning motivation in adolescents whom single mothers raise. This research method used qualitative methods with a case study approach. The research respondents were three adolescent single mothers in Purworejo Regency who were selected using a purposive sampling technique with the provision of single mothers. The results of the descriptive analysis show that adolescents who were cared for by single mothers experience problems related to learning motivation. The specific problems experienced by the three respondents were motivation and interest in learning. The lack of a mother's role in providing learning motivation affects students' low motivation to study toward their learning achievement. Based on the research results, the three respondents have different characteristics. Respondents have a high curiosity for new things. The lack of curiosity in respondents with low curiosity is due to inhibiting factors that make respondents lack interest in learning. The high level of creativity in correcting failures and mastery of learning materials owned by the three respondents had an optimistic impact on the learning process and outcomes. The lack of sympathy from the closest people, especially the mother, made the respondents indifferent to the learning outcomes they achieved, so laziness and decreased interest in learning arose in the respondents. Lack of control over study hours makes respondents often ignore study time and choose to play on their gadgets, decreasing student learning scores/achievement.